What Kinds of Support Do Novice Consultants Request and Receive? A Constructivist Grounded Theory Investigation. Issue 1 (2nd January 2022) - Ingraham, Colette L.; Johnson, Emily M.; Lopez, Kenia
ABSTRACT: Research indicates the need for better training for consultants working in culturally and linguistically diverse (CLD) schools. Using a constructivist grounded theory approach, this study investigated the use of the Consultation Peer Feedback Process (CPFP) as a tool for developing skills and perspectives among consultants. This study analyzed the types of feedback requested by consultants-in-training (CITs) and their peer-identified strengths and feedback. A coding lexicon and themes were identified to understand the needs of CITs when requesting and receiving feedback. This led to a constructivist grounded theory that describes how CITs learn to consult with cases in CLD schools. Detailed analyses of 42 CPFP Summaries indicated that the strength-based nature of the CPFP supported CITs in areas where they requested support, provided encouragement and specific feedback, and expanded CITs' exposure to cases and issues beyond their immediate setting and perspectives. Implications for research and training consultants are discussed.